Motivation teaching and learning Arabic and its impact in understanding Qur'an to tranform Ulul Albab generation: an empirical study - Sayeed, Md Mahmud (Tanjong Malim, 2023)
Motivation teaching and learning Arabic and its impact in understanding Qur'an to tranform Ulul Albab generation: an empirical study by Sayeed, Md Mahmud